1971
DOI: 10.1111/j.1365-246x.1971.tb03616.x
|View full text |Cite
|
Sign up to set email alerts
|

Dipole Offset--The Time-Average Palaeomagnetic Field Over the Past 25 Million Years

Abstract: The time-average palaeomagnetic field during Upper Tertiary times has as its source a dipole which is offset 285_+74 km north of the equatorial plane, but which remains axial. Modification of pole positions, taking the offset source dipole into account, suggests that no significant (> 1") continental drift, polar wandering, or very long-term dipole wobble have been present during the Upper Tertiary.Four different analyses of the data have shown the dipole offset to be a real phenomenon, not due to peculiaritie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
4
1

Year Published

1973
1973
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(104 citation statements)
references
References 9 publications
8
91
4
1
Order By: Relevance
“…This is shown in Figure 8, for the latitudinal band between 0 and 20°for which there were 616 data. The longitudes of the VGPs are plotted relative to their site longitude [Wilson, 1971]. The approximately circularly symmetrical form of the VGPs in this plot shows that the poles have no tendency to streak in any particular direction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is shown in Figure 8, for the latitudinal band between 0 and 20°for which there were 616 data. The longitudes of the VGPs are plotted relative to their site longitude [Wilson, 1971]. The approximately circularly symmetrical form of the VGPs in this plot shows that the poles have no tendency to streak in any particular direction.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the position of the mean pole for each latitudinal band of Table 1 has been plotted in Figure 10 and given in Table 2, in site longitude coordinates, introduced by Wilson [1971] as a convenient way of looking at this phenomenon. Nine of the poles are far sided, eight are right handed and six are both, including the three poles that are furthest away from the geographic pole.…”
Section: Resultsmentioning
confidence: 99%
“…The far-sided effect, first identified by Wilson [1970], has been attributed to the presence of a persistent axial quadrupole superimposed on the main axial dipole [Wilson, 1971] (Figure 7b and Table 5) corresponds to a lower energy spectrum [Lowes, 1974] for each degree (l = 2 to 4) of the spherical harmonic representation (Table 5; because the value of the axial dipole coefficient is set to 30 gT, the energy spectrum is not calculated for degree I = 1). The differences between the two models are more easily analyzed using the difference of the Br component at the CMB (Figure 7c).…”
Section: Implications For Taf Modelsmentioning
confidence: 99%
“…The GAD hypothesis has served as an excellent first order model, especially for the use of palaeomagnetic data in terms of continental drift (IRVING, 1964;MCELHINNY, 1973). Detailed analyses of the data covering the past few million years have shown that there are second order effects which produce significant departures from the GAD hypothesis (WILSON, 1970(WILSON, , 1971(WILSON, , 1972WILSON and MCELHINNY, 1974;Cox, 1975). MERRILL and MCELHINNY (1977) have shown that the time-averaged field is best represented by a series of zonal harmonics in a spherical harmonic expansion.…”
Section: Introductionmentioning
confidence: 99%